A systematic review investigating the behaviour change strategies in interventions to prevent misuse of anabolic steroids. (September 2019) - Bates, Geoff; Begley, Emma; Tod, David; Jones, Lisa; Leavey, Conan; McVeigh, Jim
We examined intervention effectiveness of strategies to prevent image- and performance-enhancing drug use. Comprehensive searches identified 14 interventions that met review inclusion criteria. Interventions were predominantly educational and delivered within school sport settings, but targeted a wide range of mediating factors. Identification of effective components was limited across studies by brief or imprecise descriptions of intervention content, lack of behavioural outcome measures and short-term follow-up times. However, studies with components in addition to information provision may be more promising. Interventions outside of sport settings are required to reflect the transition of this form of substance use to the general population.